2017
DOI: 10.1585/pfr.12.1401019
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Classification of Turbulence States in Linear Magnetized Plasma PANTA

Abstract: Changing the experimental conditions such as the neutral pressure and the magnetic field strength provides a drastic change in the turbulence states in linear magnetized helicon plasmas. In order to define the turbulence states and their occurrence region a throughout parameter scan in the two-dimensional parameter space was performed. The classification of the turbulence states is carried out phenomenologically based on the turbulence spectrum and the waveform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Due to the periodicity, statistical characteristics of time series data obtained by each probe are similar. The data used in this study show the formation of the streamer [7], which is an azimuthal bunching of fluctuation. In this study, the drift waves and the nonlinear quasimode (mediator), which has much longer time scale than that of the drift wave, coexist.…”
Section: Are Usedmentioning
confidence: 98%
See 1 more Smart Citation
“…Due to the periodicity, statistical characteristics of time series data obtained by each probe are similar. The data used in this study show the formation of the streamer [7], which is an azimuthal bunching of fluctuation. In this study, the drift waves and the nonlinear quasimode (mediator), which has much longer time scale than that of the drift wave, coexist.…”
Section: Are Usedmentioning
confidence: 98%
“…1 and 2 (a), reconstructions by the linear interpolation with N = 1, 2 are fairly accurate, while correlation coefficients decrease with increasing N(≥ 3). It is because the distance between two probes (coarse-graining scale 2N + 1) is longer than the wavelength of the drift waves [7] when N ≥ 3. On the other hand, reconstructions by the random forest (black marks) with six probes are much better than those by the simple linear interpolation.…”
Section: Are Usedmentioning
confidence: 99%
“…7 However, nonlinear mesoscale fluctuating structures, such as zonal flows and streamers, formed in a saturated drift wave turbulence system are found to vary according to the ion-neutral collision frequency or the neutral pressure. 6,[8][9][10] Nonlinear fluid simulation involving the neutral particle dynamics was recently implemented for calculating nonlinear turbulence evolution in the realistic experimental situation. 11 By taking into account the ionization process of neutrals in the ion fluid equation, a new instability can be derived as well.…”
Section: Introductionmentioning
confidence: 99%
“…21 In order to experimentally assess the impact of the neutrals on the turbulence and flow dynamics, neutral pressure scan experiments are occasionally performed in basic devices as one of the most simple operations. 2,9,10,14 In the case of PANTA linear magnetized plasma, increasing the neutral pressure leads to not only an increase in the neutral density but also concomitant growth of the electron density gradient. 10 Therefore, not only damping but also the growth rate of the drift wave is simultaneously varied, which is unsuitable for interpretation of the background physics.…”
Section: Introductionmentioning
confidence: 99%
“…Since turbulence structures have great influence on plasma transport [1], understanding of their formation mechanism is important for the control of fusion plasmas. Experiments in linear device PANTA have shown that there exist several types of nonlinear structures generated by drift wave instabilities, depending on parameters [2], such as streamers [3], zonal flows and solitary drift waves [4]. Numerical simulations also have shown structural bifurcation [5,6].…”
mentioning
confidence: 99%